Exploring the Drivers and Constraints in Intra-EU Trade - Makrevska disoska, Elena; Toshevska Trpchevska, Katerina; Kikerkova, Irena; Tonovska, Jasna (Association of Economists and Managers of the Balkans, Belgrade, Serbia., 2023)
The objective of this paper is to explore the factors that stimulate trade among EU countries and pinpoint areas that require improvement to foster a further increase in trade intensity within the region. The focus is on the effect of aggregate trade restrictions, which are based on the nov el indicator Measure of Aggregate Trade Restrictions (MATR), developed by the IMF. The empirical analysis consists of the estimation of a gravity panel model for the 28 EU member countries (including Great Britain) for the peri od from 1999-2020, by implementing both Ordinary least squares (OLS) and Poisson Pseudo Maximum Likelihood (PPML) estimators. The results show that the Eurozone membership has positive effects on increasing intra-EU trade, whereas the MATR indicator has significant negative effects, suggest ing that the elimination of the remaining trade restrictions could lead to a further boost of intra-EU trade.
Keywords: Intra-EU trade; Gravity model; Measure of Aggregate Trade Restrictions